Role of interleukin 1β and interleukin 10 variants on ocular toxoplasmosis in Brazilian individuals - Warlen Miiller Rocha Araujo; Christiane Maria Ayo; Mariana Previato; Mariana Previato; Geraldo Magela de Faria; Fábio Batista Frederico; Fábio Batista Frederico; Rubens Camargo Siqueira; Gildásio Castello de Almeida; Gildásio Castello de Almeida; Vera Lúcia Pereira-Chioccola; Luiz Carlos de Mattos; et al. (Frontiers in Ophthalmology, 2023)
IntroductionOcular toxoplasmosis (OT) is an intraocular inflammation caused by Toxoplasma gondii infection that affects the retina and choroid, giving rise to posterior uveitis. Genetic polymorphisms in cytokine genes may exert influence in the expression of these molecules and play a significant role in inflammatory responses and susceptibility to OT. The aim of this study was to evaluate the role of polymorphisms rs16944 (–511 C > T) of the interleukin (IL) 1β gene and rs1800896 (–1082 G > A) of the IL10 gene on OT in Brazilian individuals with a serologic diagnosis of T. gondii and after conducting fundoscopic exams.MethodsParticipants with a positive serology were classified into two distinct groups according to the presence (G1; n = 110) or absence (G2; n = 104) of OT. The control group (G3) consisted of individuals without the infection (n = 108).ResultsIt was observed that the C/C genotype of the IL1β gene polymorphism was a protective factor for OT (p = 0.02, OR = 0.28, 95% CI 0.08–0.78 for G1 vs. G2; p = 0.03; OR = 0.29, 95% CI 0.09–0.82 for G1 vs. G3), according to the recessive inheritance model.ConclusionsThe -511C.T polymorphisms of the IL1β gene seems to play an important role in the pathogenesis of OT in Brazilian individuals.